Modeling potential benefits of fragmented marsh terrace restoration in Terrebonne bay, Louisiana: sediment processes interacting with vegetation and potential submerged aquatic vegetation habitat - Jung, Hoonshin; Moss, Leland; Carruthers, Tim J. B.; Di Leonardo, Diana R.; DeMarco, Kristin; Whalen, Marie; Brasher, Michael; Dijkstra, Jasper (Frontiers in Environmental Science, 2024)
Marsh terraces, constructed as a restoration and protection strategy, consist of a series of earthen berms in open water areas of the coastal wetland landscape and are being implemented across the Louisiana coast. To assess the efficacy of the marsh terraces as a nature-based solution, a small-scale, high-resolution hydrodynamic model was developed based on field sampling of vegetation and physical parameters (water level, waves, sediment, turbidity, and terrace elevation). This study tested common marsh terrace designs (e.g., chevron, linear, box, T-shape, etc.), ultimately selecting a preferred design based on the evaluation of factors such as vegetation, water depth, and sediment type on terrace stability and sediment retention under calm and storm conditions. The model results revealed that 100 m box and chevron terrace designs exhibited substantial terrace stability and sediment trapping capabilities, particularly when installed directly against prevailing wind and waves. The chosen design was the box terrace design due to its relative resilience to wind and wave directions. Vegetation presence enhanced terrace resistance to erosion, with variations depending on vegetation type. Higher vegetation biomass, especially during the summer, contributed to the greatest stability of terraces. Deeper water depth between terraces led to increased sediment retention, and terraces predominantly composed of organic-rich mud demonstrated greater stability than those with higher proportions of sand. Overall, vegetation had the most substantial impact on sediment retention in the terrace field compared to water depth and sediment type. The potential habitat for submerged aquatic vegetation (SAV) was more influenced by water depth (i.e., 0.1 m < depth <1 m) than shear stress (< 0.5 Pa). Even under storm conditions, shear stress rarely determined potential habitat, as it remained relatively low within the terrace field. SAV potential habitat was greatest at shallow areas and increased where sediment stability was lowest (i.e., no vegetation and sand), primarily due to eroded sediment reducing overall depth. While this model was developed using field data from specific Louisiana marsh sites, its adaptability makes it a valuable tool for terrace restoration project planning in coastal areas beyond Louisiana.